Somatic Soft Tissue Leiomyoma in an Elderly Patient: A Case Report and Review of Existing Literature - Varma, Sonal; Manduch, Marosh; Varma, Sonal (International Journal of Pathology, 2018)
Leiomyomas of deep soft tissue have been traditionally divided into gynecologic and somatic leiomyomas. Somaticleiomyoma is exceedingly rare and usually has excellent outcome. We report a case of slow growing lower extremitysomatic leiomyoma in a 63-year-old man. It has been predominantly reported to affect younger agegroup. Our patient is the oldest reported patient in the English language literature. Macroscopically, the specimenconsisted of a nodular lesion with focal calcification, measuring 3.1 x 2.2 x 1.5 cm. Microscopically, this was a wellcircumscribed,mature smooth muscle tumour with a fibrous pseudocapsule and dense calcification admixed withareas of hydropic and myxoid change, and mild parenchymal and perivascular hyalinization. The smooth musclecells exhibited focal minimal atypia without increased mitotic activity or necrosis. All margins were clear of tumour.Immunohistochemically, the neoplastic cells were strongly and diffusely positive for smooth muscle markers.The case was reported as “somatic type smooth muscle tumour of soft tissue, probably benign”, and closeclinical and radiological follow-up was recommended. The patient remains clinically recurrence-free four monthsafter the diagnosis.